Endoscopic Versus Microscopic Stapedotomy: A Single-Blinded Randomized Control Trial. Issue 10 (11th December 2021) - Fan, Caleb J.; Kaul, Vivian F.; Mavrommatis, Maria A.; Schwam, Zachary G.; Hu, Shirley; Kong, Derek K.; Phan, Noel M.; Villavisanis, Dillan F.; Cosetti, Maura K.; Wanna, George B.
Abstract : Objective: To demonstrate non-inferiority of endoscopic stapedotomy to microscopic stapedotomy for the treatment of otosclerosis. Study Design: Single-blinded randomized control trial. Setting: Tertiary, academic otology-neurotology practice. Patients: Adult subjects with a diagnosis of otosclerosis and a preoperative air-bone gap (ABG) more than or equal to 20 dB undergoing primary stapedotomy. Intervention: Endoscopic or microscopic stapedotomy. Main Outcome Measures: Primary audiometric outcome was postoperative ABG. Secondary audiometric outcomes included speech reception threshold (SRT), word recognition score (WRS), bone- and air-conduction pure tone averages (PTA), change in ABG, and ABG closure rates to less than or equal to 10 dB and less than or equal to 20 dB. Results: Twenty-two patients were recruited. Eleven patients underwent endoscopic stapedotomy and 11 underwent microscopic stapedotomy. The endoscopic group was non-inferior to the microscopic group in terms of postoperative audiometric outcomes (endoscope versus microscope, p -value): ABG (8.1 dB versus 8.1 dB, <0.001), SRT (27.7 dB versus 25.9 dB, <0.001), WRS (92% at 65 dB versus 98% at 62 dB, <0.001), air-conduction PTA (33.5 dB versus 30.8 dB, <0.01), and change in ABG (23.0 dB versus 20.7 dB, <0.0001). ABG closure rates to less than or equal to 10 dB (72.7% versus 81.2%, p = 1.0) and less than or equal to 20 dB (90.9% versus 100%, p = 1.0) were not significantly different. There was no significant difference in operative time, necessity of scutum curettage, or postoperative dysgeusia. No patients required chorda tympani sacrifice. Preoperative tinnitus resolved in three patients in each group postoperatively. Conclusions: This study is the first randomized control trial to demonstrate non-inferiority of endoscopic to microscopic stapedotomy.